2016
DOI: 10.3329/ptcb.v25i2.26252
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation and Assessment of Genetic Stability of In Vitro Raised Jojoba (Simmondsia chinensis Link.) Plants Using SCoT and ISSR Markers

Abstract: This study is aimed at developing an efficient method for micropropagation of true-to-type jojoba plants. Nodal segments were used for in vitro shoots proliferation. Among three concentrations of BA used for multiplication, 1 mg/l BA gave the highest number of shoots. To enhance growth of shoots, combinations of BA and Kn were investigated. The greater value of shoot length and the maximum number of nodes were observed in the medium containing 1 mg/l BA + 1.5 mg/l Kn. Among different medium used to increase th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…By comparing both PEG and sucrose, it could be suggested that PEG has a greater in uence on the growth of G. wallichianum than does sucrose. Similar results have been observed for Lathyrus sativus (Piwowarczyk et al 2014), Milk thistle (Bekheet et al 2016), and four varieties of durum wheat (Bouiamrine and Diouri 2012). According to Razavizadeh et al (2019), adding PEG to the medium induced osmotic stress in cultured Thymus vulgaris explants, and similar conditions were found in all plants subjected to drought stress via a reduction in the fresh weight and length of thyme explants, which was consistent with other studies on several aromatic plants (Bettaieb et al 2009;Lutts et al 2004).…”
Section: Discussionsupporting
confidence: 83%
“…By comparing both PEG and sucrose, it could be suggested that PEG has a greater in uence on the growth of G. wallichianum than does sucrose. Similar results have been observed for Lathyrus sativus (Piwowarczyk et al 2014), Milk thistle (Bekheet et al 2016), and four varieties of durum wheat (Bouiamrine and Diouri 2012). According to Razavizadeh et al (2019), adding PEG to the medium induced osmotic stress in cultured Thymus vulgaris explants, and similar conditions were found in all plants subjected to drought stress via a reduction in the fresh weight and length of thyme explants, which was consistent with other studies on several aromatic plants (Bettaieb et al 2009;Lutts et al 2004).…”
Section: Discussionsupporting
confidence: 83%
“…SCoT markers can be used effectively for both genetic diversity and similarity studies [51, 52]. SCoT markers were already reported for assessing the genetic stability of several plant species such as Cleome gynandra [53], Pittosporum eriocarpum [48] , Albizia julibrissin [54], and Simmondsia chinensis [55]. Similarly, ISSR primer based assessment of regenerans was reported in Tylophora indica [56], Simmondsia chinensis [57], Rauwolfia tetraphylla L. [58], Spilanthes calva [59], Cucumis melo L. [60], Cornus alba [61], and Zea mays [62].…”
Section: Resultsmentioning
confidence: 99%
“…Micro propagation offers opportunities for production of elite and true to type plants from the selected stock plant of jojoba in a short time independent of the season 4 . In this respect, considerable differences among clones in response to growth regulators at all stages of in vitro propagation have been reported.…”
Section: Introductionmentioning
confidence: 99%